2020
DOI: 10.25046/aj050291
|View full text |Cite
|
Sign up to set email alerts
|

Face Recognition on Low Resolution Face Image With TBE-CNN Architecture

Abstract: Face recognition in low resolution images has challenges in active research because face recognition is usually implemented in high resolution images (HR). In general, research leads to a combination of pre-processing and training models. Therefore, this study aims to classify low-resolution face images using a combination of pre-processing and deep learning. In addition, this study also aims to compare evaluation results based on differences in epoch values. In this research will use the Trunk Branch Ensemble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…(Sepas-Moghaddam et al, 2020) proposes a double-deep spatio-angular framework for light field-based face recognition, which is able to model both the intra-view/spatial and inter-view/angular information using two DCNN in sequence. (Suharjito and Puspita, 2020) classify low-resolution face images using a combination of pre-processing and deep learning. They use the Trunk Branch Ensemble CNN.…”
Section: 60%mentioning
confidence: 99%
See 2 more Smart Citations
“…(Sepas-Moghaddam et al, 2020) proposes a double-deep spatio-angular framework for light field-based face recognition, which is able to model both the intra-view/spatial and inter-view/angular information using two DCNN in sequence. (Suharjito and Puspita, 2020) classify low-resolution face images using a combination of pre-processing and deep learning. They use the Trunk Branch Ensemble CNN.…”
Section: 60%mentioning
confidence: 99%
“…One very important finding was that there were 17 papers (Zafar et al, 2019;Khalajzadeh et al, 2013;Syafeeza et al, 2015;Peng et al, 2016;Bussey et al, 2017;Zeng et al, 2017;Almabdy and Elrefaei, 2019;Zeng et al, 2018a;Khan et al, 2020;Okokpujie and Apeh, 2020;Choi and Lee, 2020;Sepas-Moghaddam et al, 2020;Kim et al, 2020;Suharjito and Puspita, 2020;Darma and Mohamad, 2021;Alhanaee et al, 2021;Li et al, 2022) that reported an accuracy od 100%. With 4 papers (Bussey et al, 2017;Almabdy and Elrefaei, 2019;Sepas-Moghaddam et al, 2020;Li et al, 2022) reporting an accuracy of 100% in more than one category.…”
Section: 60%mentioning
confidence: 99%
See 1 more Smart Citation